Analisis Manajemen Waktu pada Pembangunan Gedung Pabik PT. Sumber Mulya Grand Organik di Desa Ngadri Kecamatan Binangun dengan Menggunakan Metode Jalur Kritis dan Floating CPMP - Ahmad Yufron (CV. ALIM'SPUBLISHING, 2026)
World civilization is always changing in various areas of human life. Along with the development of housing, buildings, production infrastructure and other facilities. In project development, there are several important aspects to be considered by the construction implementer in this case the contractor including time, cost, quality and work safety. Project development will achieve success if the project development implementer is able to complete the project development according to the specified schedule, available costs, quality and work safety that have been determined. The purpose of this study is to determine the critical work on the construction project of the PT. Sumber Mulya Grand Organik Factory Building using Microsoft Project 2024. In addition, it is also to determine the work network (Network Project) on the construction work of the PT. Sumber Mulya Grand Organik Factory Building in Ngadri Village, Binangun District, Blitar Regency. The data were obtained through interviews, documentation, observation and checklists. Data analysis used is using the critical path method and floating CPM. The research results, when viewed from the critical path analysis and floating CPM, show that the project construction period is 91 calendar weeks, with the critical path consisting of installing signboards, outsets/bouplanks, excavation work, tight concrete casting, concrete foot plates, installing river stone foundations, backfilling, making 15/20 concrete slopes, installing 12/15 concrete columns, installing 12/15 concrete ring beams, H-beam iron truss work, purlin work, installing rafters and H-beam iron battens, installing metal spandek roof tiles, installing zinc gutters, installing metal planks, sand filling and floor plastering, installing 60 x 60 floor tiles, wall plastering, new wall paint, installing gypsum, painting ceilings, and cleaning. All were carried out in detail and fulfilling the project's goal of completing the work quickly, meaning that the specified timeframe of 190 days was achieved in 91 days.